Aktivitas Anti Mycobacterium tuberculosis Strain H37Rv dan MDR (Multi Drug Resistant) dari Ekstrak Rimpang Curcuma mangga Val.: Anti Mycobacterium tuberculosis Activity Strain H37Rv and MDR (Multi Drug Resistant) from Curcuma mangga Val. Rhizome Extract - Pratiwi, Ritha; Alam, Gemini; Rante, Herlina; Massi, Nasrum (Universitas Tadulako, 2020)
TB is an infectious disease caused by the bacterium Mycobacterium tuberculosis. Empirically the plants that have long been used in medicine are Curcuma mangga rhizome, which shows pharmacological activity as an anti Mycobacterium tuberculosis drug. The objective of the research is to determine the ability of hexane and methanol extracts of Curcuma mangga in inhibiting the growth of Mycobacterium tuberculosis Strain H37Rv and MDR. The extraction of Curcuma mangga rhizome was conducted by maceration methode using hexane and methanol as the solvents, respectively. Both of extracts were made in 1000 dan 500 ppm concentration, then tested for anti Mycobacterium tuberculosis activity using MODS (Microscopic Observation Drug Suspectibility) method. Determination of anti M.tuberculosis activity was based on microscopic observation on Mycobacterium tuberculosis colony in cord formation. The results showed that hexane and methanol extract in 1000 ppm concentration inhibited the growth of Mycobacterium tuberculosis Strain H37Rv dan MDR. However in 500 ppm only n-hexane extract showing the inhibiton activity. In conclusion, n-hexane extract have the ability to inhibit the growth of Mycobacterium tuberculosis Strain H37Rv dan MDR.